Prodromus of a fern flora for Bolivia. XXX. Thelypteridaceae - Smith, Alan R.; Kessler, Michael (Phytotaxa, 2017)
We provide a synopsis to the family Thelypteridaceae in Bolivia, including 106 species (several with varieties) in eight genera. Five new species are described: Amauropelta boliviana, A. glabrescens, A. lanceolata, A. subacrostichoides, and Steiropteris glabra. New combinations are made for three taxa: Christella clivalis (A.R.Sm.) A.R.Sm., Christella grandis (A.R.Sm.) A.R.Sm. var. kunzeana (C.Chr.) A.R.Sm., and Christella schizotis (Hook.) A.R.Sm. Seventeen species are endemic to Bolivia.